LEAD, CADMIUM AND COPPER CONCENTRATIONS IN LEAVES OF Nerium oleander L. AND Robinia pseudoacacia L. AS BIOMONITORS OF ATMOSPHERIC POLLUTION - Kaya, Gokce; Okumus, Nuh; Yaman, Mehmet (Parlar Scientific Publications (P S P), 2010)
Pb, Cd and Cu concentrations in leaves of Nerium oleander L. and Robinia pseudoacacia L. plants collected from industrial areas in Gaziantep-Turkey were examined for biomonitoring of atmospheric pollution using flame atomic absorption spectrophotometry. The Pb levels in the leaves of Nerium oleander L. and Robinia pseudoacacia L. collected at a distance of 50 m from the battery plant were observed to be 2820 and 1860 mg kg(-1), respectively. The Pb, Cd, and Cu concentrations in the soils studied were in the range of 17-602, 0.142-0.656 and 12-38 mg kg(-1), respectively. Lead concentrations described above for plant leaves were found to be about 2000-fold higher than those in the same plants collected from the control area (1.0 mg Pb kg(-1) for both plant species). Similarly, Cd levels in Robinia pseudoacacia L. collected from polluted area were observed to be about 40 times higher than those from control area. Consequently, it is observed that the leaves of Neriurn oleander L. can be used for biomonitoring of Pb, and Robinia pseudoacacia L. for biomonitoring of both Pb and Cd pollution.
Keywords: Biomonitoring; trace metals; atomic absorption; Nerium oleander L.; Robinia pseudoacacia L.; environmental pollution